Development of the Neuro-Immune-Vascular Plexus in the Ventricular Zone of the Prenatal Rat Neocortex. (7th December 2020) - Penna, Elisa; Mangum, Jon M; Shepherd, Hunter; Martínez-Cerdeño, Veronica; Noctor, Stephen C
Abstract: Microglial cells make extensive contacts with neural precursor cells (NPCs) and affiliate with vasculature in the developing cerebral cortex. But how vasculature contributes to cortical histogenesis is not yet fully understood. To better understand functional roles of developing vasculature in the embryonic rat cerebral cortex, we investigated the temporal and spatial relationships between vessels, microglia, and NPCs in the ventricular zone. Our results show that endothelial cells in developing cortical vessels extend numerous fine processes that directly contact mitotic NPCs and microglia; that these processes protrude from vessel walls and are distinct from tip cell processes; and that microglia, NPCs, and vessels are highly interconnected near the ventricle. These findings demonstrate the complex environment in which NPCs are embedded in cortical proliferative zones and suggest that developing vasculature represents a source of signaling with the potential to broadly influence cortical development. In summary, cortical histogenesis arises from the interplay among NPCs, microglia, and developing vasculature. Thus, factors that impinge on any single component have the potential to change the trajectory of cortical development and increase susceptibility for altered neurodevelopmental outcomes.